2013
DOI: 10.1017/s1751731113000803
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ practices, motivators and barriers for adoption of treatments of digital dermatitis in dairy farms

Abstract: This study aimed to catalogue the digital dermatitis (DD) treatment practices used by French dairy farmers and to identify the motivators and barriers to the adoption of these treatments. A semi-structured survey was conducted involving 65 farmers in the main dairy production areas of France in the spring of 2009. The different treatment modalities implemented by farmers since the first diagnosis of DD in their herds were described. The reasons for adopting or abandoning these treatments were then investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…Positive perceptions of the effectiveness of proposed measures to control mastitis was not only linked to dairy farmers' adoption intent, but also strongly associated with mastitis incidence (Jansen et al, 2009). Similarly, the reason most commonly given by farmers for the adoption of a digital dermatitis protocol in cattle was its perceived effectiveness (Relun et al, 2013). However, the diversity of prevention and treatment protocols for foot health likely enhances farmers' insecurity about best practices and emphasizes the need for standardized recommendations based on credible research (Solano et al, 2017; Table 2).…”
Section: Effectiveness Of Recommended Strategiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Positive perceptions of the effectiveness of proposed measures to control mastitis was not only linked to dairy farmers' adoption intent, but also strongly associated with mastitis incidence (Jansen et al, 2009). Similarly, the reason most commonly given by farmers for the adoption of a digital dermatitis protocol in cattle was its perceived effectiveness (Relun et al, 2013). However, the diversity of prevention and treatment protocols for foot health likely enhances farmers' insecurity about best practices and emphasizes the need for standardized recommendations based on credible research (Solano et al, 2017; Table 2).…”
Section: Effectiveness Of Recommended Strategiesmentioning
confidence: 98%
“…Disease prevention and control measures will be implemented only if farmers perceive them to be feasible and practical (Garforth et al, 2013;Toma et al, 2015; Table 3). For example, dairy cow hoof mats soaked in trademarked chemical solutions were often abandoned because of difficulty manipulating and cleaning them, or because cows were reluctant to walk over them (Relun et al, 2013).…”
Section: Recommendation Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Individual cow treatments are often seen as too time consuming by farmers (Leach et al, 2010;Relun et al, 2013a), and walk-through hoof baths have therefore been used extensively to control DD. Several different hoof-bath chemicals have been used in such hoof baths.…”
Section: Short Communicationmentioning
confidence: 99%
“…Several different hoof-bath chemicals have been used in such hoof baths. For decades, copper sulfate has been one of the most popular compounds used in hoof baths (Laven and Logue, 2006;Cook et al, 2012;Relun et al, 2013a), and it has been stated that copper sulfate is widely reported to be effective (e.g., Logue et al, 2012). Based on its frequent use, copper sulfate has been referred to as the industry gold standard when it comes to hoof-bath chemicals (Teixeira et al, 2010;Smith et al, 2014).…”
Section: Short Communicationmentioning
confidence: 99%